Exploring the relationship between visual inspection time task and intelligence in young children - Spanoudis, George; Tourva, Anna (Psychology: the Journal of the Hellenic Psychological Society, 2023)
Inspection time task (IT) indexes individual differences in perceptual discrimination speed and it is a reliable predictor of psychometric intelligence However, the reasons underlying the relationship between IT and intelligence are not clear, because few studies investigated factors shared by both of them. This study examined how performance on a modified version of the inspection time task relates to individual differences in attentional control and how this relation is affected by age. A total of 157 children from 7 through 18 years were tested in a visual inspection time task, a Go/no-go reaction time task, a letter-matching task, and the Wechsler Abbreviated Scale of Intelligence (WASI). Diffusion modeling showed that IT captures top-down sensory and attentional processes underlying the IT-IQ relation and that individual differences in drift rate of ECTs predict individual differences in intelligence. Therefore, IT and attention make unique contributions to the prediction of IQ variability.